2007
DOI: 10.1213/01.ane.0000263279.07361.1f
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Stroke Risk Among the Elderly After Coronary Artery Surgery

Abstract: These data suggest that men are more likely than women to have risk factors for stroke, including severe carotid artery stenosis, severe aortic atherosclerosis, and peripheral vascular disease. The rates of prior cerebral infarction and preoperative cognitive impairment were similar between genders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 21 publications
2
10
0
Order By: Relevance
“…37 Goto et al revealed that female patients were significantly more likely than male patients to have significant intracranial arterial stenosis, whereas male patients had significantly more severe atherosclerosis of the ascending aorta than female patients. 38 These studies suggest that the distribution and plaque characteristics of atherosclerosis causing postoperative cerebrovascular complications may differ between the genders.…”
Section: Discussionmentioning
confidence: 99%
“…37 Goto et al revealed that female patients were significantly more likely than male patients to have significant intracranial arterial stenosis, whereas male patients had significantly more severe atherosclerosis of the ascending aorta than female patients. 38 These studies suggest that the distribution and plaque characteristics of atherosclerosis causing postoperative cerebrovascular complications may differ between the genders.…”
Section: Discussionmentioning
confidence: 99%
“…The difference could be attributed to reported gender difference in risk profiles between males and females. Males, in literature, are associated with smoking, heavy alcohol intake and higher risk of peripheral vascular diseases [28].…”
Section: Social Demographic Data Of Stroke Patients In Kenyamentioning
confidence: 99%
“…Atherosclerosis of the ascending aorta is an established risk factor for stroke and has been implicated to be associated with neurocognitive dysfunction by some but not all investigations [1, 2, 7, 25, 26]. Several lines of evidence suggest that the distribution and plaque characteristics of atherosclerosis differ between sexes [9, 11]. …”
Section: Commentmentioning
confidence: 99%
“…Thus, risk stratification for women is mostly based on data obtained primarily from men, despite the findings that women present for cardiac operation with a different distribution of atherosclerotic and vascular risk factors for brain injury [912]. We have previously assessed sex-specific risk factors for stroke after cardiac operation [4, 6].…”
mentioning
confidence: 99%